Factors influencing and spatial distribution of tuberculosis mortality in Kelantan from 2013 to 2014 - Nasir, Zainurulazma Mohd (2018)
Tuberculosis (TB) is a common communicable disease and one of the public health burdens to the Ministry of Health. This study was to determine the factors associated with mortality among tuberculosis cases. In Malaysia it is still major challenge to public health especially unsuccessful treatment rate increases by year. To determine the spatial distributions and factors associated of mortality among TB cases. A crosssectional study was conducted. All eligible TB cases data from all District Office in Kelantan from year 2013 to year 2014 were collected to determine the outcome of the TB treatment. Data were analyzed using software ArcGIS 10.1 and IBM SPSS version 22.0. All coordinate data; longitude and latitude both of TB cases and health facilities from Garmin GPSmap 60CSx were transferred into MS excel 2010. Euclidean distances between TB cases and health facilities were measure based on Euclidean distances and saved in same file. Then the data were imported into ArcMap 10.1 as a shapefile data layer. The data layers with the coordinate on a map were saved into JPEG file format. Simple and multiple logistic regressions were applied to present the associated factors that contributed to the mortality of TB cases. A total of 1645 of TB cases from year 2013 to 2014 were recorded in which the mortality of cases were 13.1%. Majority TB cases were male 65.0%, mean (SD) age was 48.7 (18.05) years old and highest number of cases located in Kota Bharu (25.1%). Approximately, 25% were sputum culture positive, 12% HIV positive and nine percent was noncompliance with DOTs maintenance treatment. TB cases also was plotted based on Euclidean distance used ArcMap 10.1 on Kelantan map and the result were 32% of TB cases were located more than 10 km from health facilities. Semi-variogram shows that there is not significant Euclidean distance between cases with another case. Euclidean distance had suggested no relationship with spatial autocorrelation. Result shows that cases with older age (OR=1.05, 95%C.I=1.03, 1.08), sputum culture positive (OR=2.11, 95%CI=1.15, 3.89), HIV positive (OR=20.50, 95%CI=9.10, 46.20), non-compliance to DOTs maintenance treatment (OR=24.17, 95% CI=11.84, 49.35) and distance more than 10 km (OR=2.54, 95%CI=1.39, 4.64) were significantly associated with mortality among TB cases. In conclusion, those with older age, sputum culture and HIV positive, noncompliance with DOTs maintenance treatment and far away from health facilities are posing higher chance of mortality among TB cases.